2021
DOI: 10.1186/s12870-021-03200-5
|View full text |Cite
|
Sign up to set email alerts
|

Altered metabolomic states elicited by Flg22 and FlgII-28 in Solanum lycopersicum: intracellular perturbations and metabolite defenses

Abstract: Background Surveillance of potential pathogens is a key feature of plant innate immunity. For non-self-recognition plants rely on the perception of pathogen-derived molecules. Early post-perception events activate signaling cascades, leading to the synthesis of defense-related proteins and specialized metabolites, thereby providing a broad-spectrum antimicrobial coverage. This study was concerned with tracking changes in the tomato plant metabolome following perception of the flagellum-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…The overall luminescence results ( Figures 1B, C ) confirmed the host plant’s ability to respond to the LPS R. sol. elicitor through the production of ROS, albeit at a lower metabolic level compared to flagellin-derived peptides flg22 and flg28 ( Zeiss et al, 2021a ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall luminescence results ( Figures 1B, C ) confirmed the host plant’s ability to respond to the LPS R. sol. elicitor through the production of ROS, albeit at a lower metabolic level compared to flagellin-derived peptides flg22 and flg28 ( Zeiss et al, 2021a ).…”
Section: Resultsmentioning
confidence: 99%
“…This selection was made using the OPLS-DA loading S-plots ( Figure 6B ) and VIP scores ≥2. The cut-off values of |p(corr)| and |(p1)| previously mentioned were determined based on the application of descriptive statistics (ANOVA), which also included the calculation of control- and treatment-averaged peak intensities, the standard deviation, the coefficient of variation, the fold change between the two groups, and the p value on the selected features ( Zeiss et al, 2021a ). In the parameter determination process, a statistical cut-off of p value ≤0.05 was used for ANOVA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that elicitors such as flg22 and oligogalacturonides (OGs) positively regulate key genes of secondary metabolism involved in the biosynthesis of glucosinolates, camalexin and phenylpropanoids such as cytochrome P450 (CYP) and PAL genes [45]. Recent metabolomics analysis also showed positive impact of flg22 treatment on secondary metabolites production in tomato [50].…”
Section: Discussionmentioning
confidence: 99%
“…More recent work in the cells of Sorghum bicolor treated with LPS showed enrichment of hydroxycinnamic acids and other phenylpropanoids in coordination with accumulation of both SA and JA (Mareya et al 2020). Treatment of tomato with flg22 and flgII-28 also enriched hydroxycinnamic acids, and tomato treatment with cps22 revealed a metabolic shift toward the phenylpropanoid pathway with hydroxycinnamic acid, conjugates and derivatives as key biomarkers (Zeiss et al 2021a, b). Similar to traditional MAMPs, AA and the AA/EPA-containing complex mixture, ANE, both induce enrichment of cinnamic acid and derivatives in tomato seedlings (Fig.…”
Section: Discussionmentioning
confidence: 99%